ANALISIS PEMBELAJARAN DARING MENGGUNAKAN BANTUAN MEDIA ELEKTRONIK SELAMA PANDEMI COVID-19 - Muhammad Amanatullah; Arya Setya Nugroho; Nanang Khoirul Umam (LPPM UNISDA, 2022)
ABSTRACT The background of this research is the COVID-19 pandemic that hit Indonesia. The world of education has had a huge impact. The government's solution to keep the learning process going is online learning. The purpose of this research is to find out whether online learning can support the learning process at home. So the researchers conducted a study entitled